Study protocol for FIBROKIT: a new tool for fibromyalgia diagnosis and patient follow-up - del Amo, Laura Lucena; Durán-González, Elena; Ramírez-Tejero, Jorge A.; Martínez-Lara, Antonio; Cotán, David (Frontiers in Neurology, 2023)
Fibromyalgia (FM) is a complex disease that is characterized by chronic musculoskeletal pain and has great economic impact. FM prevalence is about 2% to 4% worldwide, affecting mainly middle-aged women, and its complex pathophysiology complicates diagnosis, treatment and the findings of solid biomarkers. Previous studies have suggested an association between the disease and oxidative stress, mitochondrial metabolism, intestinal microbiota and inflammation, providing sufficient data to support the multifactorial origin of FM. Hence, the objective of this randomized, prospective, low-interventional, double-blinded and placebo-controlled clinical trial is the development of a specific panel of FM biomarkers and the evaluation of their response to a six-month nutritional intervention based on the Mediterranean diet supplemented with extra virgin olive oil (EVOO). For this purpose, the experimental design implies the recruitment of a large cohort of female Spanish patients. Middle-aged women who meet the diagnostic criteria for FM according to the American College of Rheumatology (ACR) will be eligible, along with age-matched healthy women. Both groups will be randomly divided into placebo (olive oil, OO) and treatment groups (extra virgin olive oil, EVOO), and will provide samples at the beginning (T0), after three months of nutritional intervention (T1), at the end of the nutritional intervention in six months (T2), and six months after the end of nutritional intervention (TF), being enrolled for one year. Data will be collected through health questionnaires, and whole blood and stool samples will be taken and analyzed. Blood will be used for western-blotting and proteomic analysis of mitochondrial homeostasis and plasma proteome, while stool will undergo metagenomic analysis, respectively. This study represents the first low-interventional investigation with more than 200 participants focused on exploring the association of oxidative stress, mitochondrial metabolism, intestinal microbiota and related pathways with a nutritional intervention in the context of FM. As a result, the outcomes of this study will significantly contribute to the development of a comprehensive of robust a robust panels of diagnostic biomarkers, and will shed some light on their modulation with non-pharmacological therapies such as nutrition.